Motivasi Kerja Badan Musyawarah Kampung dalam Pelaksanaan Pembangunan - hesty tambajong; Dewi Putri Anjar Wulan (SOCIETAS, 2020)
This article aims to determine the work motivation of the role of the Village Deliberative Council (Bamuskam) in local villages and migrant villages and to identify factors that have an impact on the role of the Village Deliberative Council (Bamuskam) in implementing development. This article uses a qualitative descriptive type, which is a type of research that explores and clarifies an event or phenomenon in social facts with techniques to collect data used are observation, interviews, and literature study. This article shows that the motivation for the work of the Village Deliberative Council (Bamuskam) in local villages and immigrant villages is optimal by agreeing and discussing a draft Village Regulation (Perkam) together with the Village Head, as a container for and channeling community aspirations, and also as a supervisor. from the performance of the Village Head related to the Bamuskam function regarding supervision. Besides, several factors affect the function and role of the Village Deliberative Council (Bamuskam) in carrying out development which consists of supporting factors, namely the education level of Bamuskam members during the selection process for Bamuskam members, community factors, factors of cooperation with village officials, and social factors. culture. As for the inhibiting factors, namely the Bamuskam members who did not participate in the meeting, and the facilities factor, namely the absence of a Bamuskam secretariat office both in the local village and in the migrant village.